Apoplastic Hydrogen Peroxide in the Growth Zone of the Maize Primary Root. Increased Levels Differentially Modulate Root Elongation Under Well-Watered and Water-Stressed Conditions - Voothuluru, Priya; Mäkelä, Pirjo; Zhu, Jinming; Yamaguchi, Mineo; Cho, In-Jeong; Oliver, Melvin J.; Simmonds, John; Sharp, Robert E. (Frontiers in Plant Science, 2020)
Reactive oxygen species (ROS) can act as signaling molecules involved in the acclimation of plants to various abiotic and biotic stresses. However, it is not clear how the generalized increases in ROS and downstream signaling events that occur in response to stressful conditions are coordinated to modify plant growth and development. Previous studies of maize (Zea mays L.) primary root growth under water deficit stress showed that cell elongation is maintained in the apical region of the growth zone but progressively inhibited further from the apex, and that the rate of cell production is also decreased. It was observed that apoplastic ROS, particularly hydrogen peroxide (H2O2), increased specifically in the apical region of the growth zone under water stress, resulting at least partly from increased oxalate oxidase activity in this region. To assess the function of the increase in apoplastic H2O2 in root growth regulation, transgenic maize lines constitutively expressing a wheat oxalate oxidase were utilized in combination with kinematic growth analysis to examine effects of increased apoplastic H2O2 on the spatial pattern of cell elongation and on cell production in well-watered and water-stressed roots. Effects of H2O2 removal (via scavenger pretreatment) specifically from the apical region of the growth zone were also assessed. The results show that apoplastic H2O2 positively modulates cell production and root elongation under well-watered conditions, whereas the normal increase in apoplastic H2O2 in water-stressed roots is causally related to down-regulation of cell production and root growth inhibition. The effects on cell production were accompanied by changes in spatial profiles of cell elongation and in the length of the growth zone. However, effects on overall cell elongation, as reflected in final cell lengths, were minor. These results reveal a fundamental role of apoplastic H2O2 in regulating cell production and root elongation in both well-watered and water-stressed conditions.